Endodontic systemic medication - García, Fernando Antonio Vázquez [UNESP]; Otarola, Wilfredo Gustavo Escalante [UNESP]; Keine, Katia Cristina [UNESP]; García, Arturo Javier Aranda [UNESP]; Kuga, Gabriel Keine [UNESP]; Kuga, Milton Carlos [UNESP] (My University, 2020)
Introduction: Endodontic complications, such as the presence of inflammation, pain, infection and anesthetic difficulties, require rationalization in systemic drug therapy. Objective: To describe the indications, contraindications and side effects of prescribing and using medications in the main clinical situations before, during and after root canal treatment. Methods: A compilation of bibliographic references was made after a search carried out in using the PubMed search engine, which has free access to MEDLINE. The following keywords were used: medicación sistémica endodóntica [endodontic systemic medication], pulpitis irreversible sintomática [symptomatic irreversible pulpitis]; periodontitis apical sintomática [symptomatic apical periodontitis], and absceso apical agudo [acute apical abscess]. We retrieved 274 articles, of which 68 were considered relevant, since they contemplated the solving of endodontic problems. Conclusions: The elaboration of protocols about the fundamentals of scientific research and based upon clinical evidence allows treating root canals with safety and well-being for the patient, thus increasing clinical success rates.
Medicación sistémica en endodoncia
Keywords: Acute apical abscess; Endodontic systemic medication; Symptomatic apical periodontitis; Symptomatic irreversible pulpitis